With a little help from my friends? Acculturation and mental health in Arabic-speaking refugee youth living with their families - Meyer, Caroline; Alhaddad, Lina; Stammel, Nadine; Sixtus, Frederick; Wesche, Jenny Sarah; Kerschreiter, Rudolf; Kanngiesser, Patricia; Knaevelsrud, Christine (Frontiers in Psychiatry, 2023)
Refugee youth are often faced with the compounding challenges of heightened exposure to traumatic events and acculturating to a new country during a developmental period when their sense of self is still forming. This study investigated whether refugee youth’s acculturation orientation (separation, integration, marginalization, and assimilation) is associated with depressive and posttraumatic stress symptoms and aimed to identify additional indicators of acculturation that may contribute to mental health. A total of 101 Arabic-speaking refugee youths (aged 14-20 years), who were living with their families and attending school in Germany, took part in the study. They answered questions concerning traumatic exposure and posttraumatic stress symptoms, depressive symptoms, and several indicators of acculturation, including cultural orientation, positive and negative intra- and intergroup contact, language skills and friendship networks. All participants were categorized into one of four acculturation orientations using median splits. Kruskal-Wallis rank sum tests revealed that acculturation orientation was not significantly associated with depressive symptoms (χ² [3, 97] = .519, p = .915) or posttraumatic stress symptoms (χ² [3, 97] = .263, p = .967). Regression analysis revealed that German language skills were significantly associated with lower scores of depressive symptoms (p = .016) and number of friends in Germany was significantly associated with lower scores of depressive (p = .006) and posttraumatic stress symptoms (p = .002), respectively. Policies that provide refugee youth with access to language classes and social activities with peers do not only enable them to actively participate in a new society but may also have a positive effect on their mental health.